2020
DOI: 10.1002/soej.12421
|View full text |Cite
|
Sign up to set email alerts
|

Corruption as an Occupational Choice: Endogenous Corruption and Tax Policy

Abstract: Corruption is endemic in many countries, and empirical studies have demonstrated how it impacts on macroeconomic indicators. Theoretical studies have generally assumed an exogenously given proportion of the population are corrupt or that the public sector is fixed in size; far fewer explore how corruption emerges endogenously. We endogenize corruption as an occupational choice. Workers choose private or public employment; public employees can be honest or corrupt. Corruption is subject to a social sanction tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Furthermore, Property Rights, Trade Freedom, and Investment Freedom are the factors that have a significant impact on corruption perception. Similar to the studies in the literature, it is shown that the nexus between marginal tax rate (or total tax burden as a percentage of GDP), which is the major metrics of the Tax Burden dimension, and the corruption perception is highly correlated (Damayanti et al, 2020;Myles & Yousefi, 2020;Le et al, 2020). The relationship between Tax Burden and Corruption is described as it appears that there is less corruption when there is a low tax burden, thus taxpayers are intrinsically motivated to act more honestly and provide accurate information in these studies.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, Property Rights, Trade Freedom, and Investment Freedom are the factors that have a significant impact on corruption perception. Similar to the studies in the literature, it is shown that the nexus between marginal tax rate (or total tax burden as a percentage of GDP), which is the major metrics of the Tax Burden dimension, and the corruption perception is highly correlated (Damayanti et al, 2020;Myles & Yousefi, 2020;Le et al, 2020). The relationship between Tax Burden and Corruption is described as it appears that there is less corruption when there is a low tax burden, thus taxpayers are intrinsically motivated to act more honestly and provide accurate information in these studies.…”
Section: Discussionsupporting
confidence: 65%